Habitat analysis and domestication studies on orilathamara (Nervilia aragoana gaud) - Anulakshmi Sankar (Department of Plantation crops and spices,College of Horticulture, 2011)
The present investigations on “Habitat analysis and domestication studies on ‘Orilathamara’ (Nervilia aragoana Gaud.)” was carried out at the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara during 2009 – 2011, with the objectives to collect the source plants of the drug Orilathamara from wild, to carry out detailed natural habitat analysis and to analyze the response of the species to domestication.